Models of Relationship between Physicians and Patients Referring to the Clinic of Isfahan Shahid Beheshti Hospital 2007 - Zahra Karami; Mahmoud Keyvanara (Kerman University of Medical Sciences, 2010)
Background & Objective : An appropriate relationship between a physician and a patient will lead to earning patients trust prevention of frequent referrals to multiple physicians and patients bewilderment and lastly it results in saving time and money Hence this study was conducted to determine the dominant model of relationship between physicians and patients according to patients opinion   Methods : In this crosssectional study 305 patients who for the first time referred to the physicians of the clinic of Isfahan Shahid Beheshti Hospital for their recent illness were recruited Data was collected using a researchermade questionnaire including 10 general and 19 attitudeassessing questions The questionnaires reliability and validity were already confirmed   Results : The dominant models of relationship between patients and physicians were guidancecooperation (865%) activepassive (111%) and mutual participation (24%) in order of frequency There was no significant difference between the relationship model and the patients educational or social class Guidancecooperation and activepassive models were significantly more frequent in older and younger individuals respectively (P=0047)   Conclusion : A ccording to mutual participation model (the most effective model of relationship between physicians and patients) and considering its low frequency in our study we can conclude that enhancing patients awareness about their health status and encouraging them to participate in the treatment process (which results in increasing both sides responsibility for a common goal) would improve the relationship between physicians and patients Having earned both physicians and patients trust all mentioned issues would finally facilitate health access